The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species - Abul-Sood, Medhat I.; Gadallah, Neveen S.; Hossni, Mohammed T.; Delvare, Gérard (Zootaxa, 2018)
The Cratocentrinae (Hymenoptera: Chalcididae) of the West Palaearctic region are reviewed. A reappraisal of the morphological characters used for their recognition and phylogeny is provided as is a key to separate the genera and species of the region. Their distribution in the West Palaearctic is updated and the subfamily is reported for the first time in Europe. Cratocentrus inermus Delvare sp. nov. and Philocentrus papillus Abul-Sood & Gadallah sp. nov. are described. A neotype is designated for Philocentrus argenteopilosus (Cameron), which is revalidated and transferred to Philocentrus comb. nov. & stat rev.